Evaluation of IPM modules against shoot pests of rabi sorghum (Sorghum bicolor L. Meonch) - Subbarayudu, B; Shyam Prasad, G; Parashuram, P; Kalaisekar, A; Srinivas, A; Rajappa, P V; Sevanayak, D; Basawaraj, R; Raghunath, K; Mukesh, P (Indian Journal of Plant Protection, 2024)
Shoot fly Atherigona soccata (Rondani) and Stem borer, Chilo partellus (Swinhoe) and shoot bug, Peregrinus maidis (Ashmead) are major shoot pests of post rainy sorghum grown in dryland region of Solapur, Maharashtra. Therefore, attempts were made to develop cost effective management measures. A series of trials were carried out during the rabi 2021-23 seasons at Centre on Rabi Sorghum, Solapur, Maharashtrato find out the cost- effective Integrated pest management technology modules. The chemical based module 1 comprised of use of CSV 29 R, high seed rate @ (10 kg/ha), seed treatment with imidacloprid @ 6 ml/ kg of sorghum seed, whorl application of fipronil 0.3 GR @ 7.5 kgs/ha at 21 Days After Emergence (DAE) and spray of emamectin benzoate 5 % SG (0.3 g/lit of water) at 35 DAE. The biointensive module 2 wascomprising use of CSV 29 R, seed treatment with thiomethoxam 19.8 w/w and cyantranilprole 19.8 w/w @ 6 ml/kg of seed followed by release of egg parasitoid, Trichogramma chilonis released twice at 20 and 30 DAE @ 1,25,000/ha and spray of entomopathogenic fungi, Metarhizium anisopliae- Ma 35 (1 x 108 ml/1), @ 5ml/liter at 45 and 60 DAE. The farmer’s practice based module 3 comprised the treatments viz.; use of CSV 29 R, seed rate @ 7.5 kgs/ha followed by spray of emamectin benzoate 5% SG @ 0.3 g/lit of water at 30 DAE. Of these three modules tested for the shoot pests of sorghum that at 21 DAE, the module 1 (chemical based) recorded the least number of shoot fly eggs/3 plants (7.10) its deadhearts (5.9%), stemborer deadhearts recorded at 45 DAE (10.10 % DH); shoot bug adults /3 plants recorded at 60 DAE (3.90) and its nymphs (4.90). The grain yields/ha were recorded highest in chemical based module (3.35 tonnes/ha; followed by biointensive module (3.20 tonnes/ha) and with farmers practice based module (1.95 tonnes/ha). The economics of these modules were also calculated and found that chemical based module was observed cost effective and profitable (B:C Ratio=1:1.80) followed by biointensive module (B:C Ratio=1:1.66) and farmer’s practice (B:C Ratio=1:1.20). The incidence of shoot pests and their cost benefit ratio in the biointensive module is at par with the chemical based module. Overall, biointensive module would be recommended to the sorghum growers in view of the ecosystems safety and consumption of sorghum grain as the major staple food for the dryland region of Solapur, Maharashtra.